2009
DOI: 10.1097/acm.0b013e3181b6a9af
|View full text |Cite
|
Sign up to set email alerts
|

The Personal Interview: Assessing the Potential for Personality Similarity to Bias the Selection of Orthopaedic Residents

Abstract: The results support the hypothesis that, within the department studied, there was a significant association between similarities in personality type and the rankings that individual faculty interviewers assigned to applicants at the completion of each interview session. The authors believe that it is important for the faculty member to recognize that this tendency exists. Finally, promoting diversity within the admission committee may foster a diverse resident body and orthopaedic workforce.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(39 citation statements)
references
References 26 publications
0
39
0
Order By: Relevance
“…It has also been suggested that the problem of bias may occur, for instance, where a candidate is fortunately placed with an interviewer of 'like mind' or with one who can influence an interview panel, whereas an incompatible relationship can prove unfavourable (Quintero et al 2009). They suggested that an interview outcome can be influenced by a "halo effect" where decisions of the panel are influenced more by general feelings of 'like or dislike' than on the answers given by or actual qualities of the interviewee.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It has also been suggested that the problem of bias may occur, for instance, where a candidate is fortunately placed with an interviewer of 'like mind' or with one who can influence an interview panel, whereas an incompatible relationship can prove unfavourable (Quintero et al 2009). They suggested that an interview outcome can be influenced by a "halo effect" where decisions of the panel are influenced more by general feelings of 'like or dislike' than on the answers given by or actual qualities of the interviewee.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Use of the Myers-Briggs personality inventory for interviewers and applicants demonstrated that clinician faculty ranked candidates more favorably when they shared certain personality styles. 103 Bohm et al 106 evaluated a moral reasoning assessment tool in orthopedic resident applicants and found no association between moral reasoning and resident rank or USMLE scores.…”
Section: Personality Testingmentioning
confidence: 99%
“…Eight studies explored the use of personality [99][100][101][102][103] or emotional intelligence [104][105][106] testing as part of resident selection. Use of the Myers-Briggs personality inventory for interviewers and applicants demonstrated that clinician faculty ranked candidates more favorably when they shared certain personality styles.…”
Section: Personality Testingmentioning
confidence: 99%
“…20 Similarly, other studies have attempted to identify unique personality characteristics of residents already in particular specialties, such as dentistry, internal medicine, anesthesiology, urology, and orthopedic surgery. [21][22][23][24][25][26] Studies attempting to define the surgical personality or identify personality traits unique to surgeons have varied results and conclusions. One of the earliest studies in surgery polled surgeons themselves on which traits were most important for surgeons.…”
Section: Discussionmentioning
confidence: 99%